Ligninolytic Enzymes Produced by Gliomastix sp. in an Organic Waste Medium - Nengah Dwianita Kuswytasari; Maya Shovitri; Enny Zulaika (IPTEK The Journal for Technology and Science, 2015)
Ligninolytic enzymes are extracelluler enzymes that have many benefit on multiple industrial department. Its can result from Gliomastix sp. This study was aimed to determine the effect of temperature and pH on the activity of Ligninolytic enzymes by Gliomastix sp. T3.7 that grow on multiple organic waste . Ligninolytic enzymes was measured with spectrofotometer UV-Vis Boeco S22. The result showed that Gliomastix sp. T3.7 potentially produce the ligninolytic enzymes like as laccase, LiP and MnP. The optimum laccase activity ( 1,765 U/ml) detected on sugarcane baggase waste, pH 6 and temperature of 350C . The optimum LiP activity (8,088U/ml) detected on corn cobs, pH 5 and 350C, whereas the optimum MnP activity (0,964 U/ml) detected on sugarcane baggase too. Its optimum on pH 4 and 250C. Gliomastix sp. T3.7 on sugarcane bagasse, pH 6 and 350C, agensia potentially used as remediation on a variety of industry pollution.